THE INFLUENCE OF YOUTUBE LEARNING MEDIA ON THE UNDERSTANDING OF THE MATERIAL, THE SIZE OF CENTRAL SYMPTOMS AND THE RELIABILITY OF STATISTICS SUBJECTS FOR STUDENTS - Ina Marlina Lubis; Ambiyar; Mahesi Agni Zaus (AKADEMI TEKNIK ADI KARYA, 2024)
This research aims to (1) determine the feasibility of YouTube learning media on central symptom measurements and reliability. (2) Find out the effect of YouTube learning media on central symptom measurements and reliability. This research was conducted on students. The research method used was Research &; Development with the EDDIE development model. The results of this research: (1) Development of YouTube media on material measuring central symptoms and manufacturing reliability according to 3 material experts with an average of 95% in the category